If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x+9=16-x
We move all terms to the left:
6x+9-(16-x)=0
We add all the numbers together, and all the variables
6x-(-1x+16)+9=0
We get rid of parentheses
6x+1x-16+9=0
We add all the numbers together, and all the variables
7x-7=0
We move all terms containing x to the left, all other terms to the right
7x=7
x=7/7
x=1
| 140=(n-2)180÷n | | 10x=x^2-11 | | 7m+3(m+2)=-21 | | x-19=5-3x | | 288=-8(6x+5)-8 | | 4(2x-3)-1=-7 | | 12b-7=29 | | 4^4x-3=4^8-9x | | x-19=5x+16 | | 2x=x/3-45 | | 1.5d+9.75d=1+3.25d | | 2x=45-(x/3) | | 4/4=n/6 | | x+x+x+6=78 | | 4=8q-6q | | y=59+1 | | 6b-10=2(b-11)+4(b-2) | | 16y-24=-18+9y | | 2x^2-4=30 | | -7/8z=-1/5 | | 25x+21=-15(8x-25)-2x | | x/3-45=2x | | h+8=-27 | | x/3=45-2x | | 12.9x=16 | | (x2+5)-6=(9x+18)3 | | 2x-8=x+59 | | 5y+7=-14+8y | | 4(-8+5)=32x=26 | | 8(3x-7)=-6(x+7) | | -2x^2+52x+240=0 | | 5m−m=8 |